2016
DOI: 10.1002/hbm.23225
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of spatial and nonspatial attention determined using intracranial electroencephalographic signals in humans

Abstract: Few studies have directly compared the neural correlates of spatial attention (i.e., attention to a particular location) and nonspatial attention (i.e., attention to a feature in the visual scene) using well‐controlled tasks. Here, we investigated the neural correlates of spatial and nonspatial attention in humans using intracranial electroencephalography. The topography and number of electrodes showing significant event‐related desynchronization (ERD) or event‐related synchronization (ERS) in different freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…Various studies have revealed that the dorsal attention network, which consists of the FEF and SPL/IPS, is involved in top‐down visuospatial orienting attention (Corbetta & Shulman, ; Fan, McCandliss, Fossella, Flombaum, & Posner, ; Phillips et al, ). Additionally, some studies have reported the dorsal attention network has a spatial‐specific orienting function (Corbetta, Kincade, Ollinger, McAvoy, & Shulman, ; Giesbrecht et al, ; Hopfinger, Buonocore, & Mangun, ; Kastner, De Weerd, Desimone, & Ungerleider, ; Scolari et al, ; Yantis et al, ) and our previous study (Park et al, ) support these findings.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Various studies have revealed that the dorsal attention network, which consists of the FEF and SPL/IPS, is involved in top‐down visuospatial orienting attention (Corbetta & Shulman, ; Fan, McCandliss, Fossella, Flombaum, & Posner, ; Phillips et al, ). Additionally, some studies have reported the dorsal attention network has a spatial‐specific orienting function (Corbetta, Kincade, Ollinger, McAvoy, & Shulman, ; Giesbrecht et al, ; Hopfinger, Buonocore, & Mangun, ; Kastner, De Weerd, Desimone, & Ungerleider, ; Scolari et al, ; Yantis et al, ) and our previous study (Park et al, ) support these findings.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have revealed that, while performing the tasks after cue‐onset, the right frontoparietal network is important for both tasks, and that spatial attention, when compared to nonspatial attention, is lateralized to a greater extent to the right hemisphere (Park et al, ). However, it is not entirely clear whether—and if so, to what extent—a difference in connectivity in the right frontoparietal network from the preparatory state to the cognitive state exists between the two tasks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations